Effects of bank supervision and regulation on bank risk - Kujala, Jukka (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
In the last few decades, banking has strongly internationalized and become more complex. Hence, bank supervision and regulation has taken global perspective, too. The most important international regulation are the Basel frameworks by the Basel committee on banking supervision. This study examines the effects of bank supervision and regulation, especially the Basel II, on bank risk and risk-taking. In order to separate and recognize the efficiency of these effects, the co-effects of many supervisory and regulatory tools together with other relevant factors must be taken into account. The focus of the study is on the effects of asymmetric information and banking procyclicality on the efficiency of the Basel II. This study tries to find an answer, if the Basel II, implemented in 2008, has decreased bank risk in banks of European Union member states. This study examines empirically, if the volatility on bank stock returns have changed after the implementation of the Basel II. Panel data consists of 62 bank stock returns, bank-specific variables, economic variables and variables concerning regulatory environment between 2003 and 2011. Fixed effects regression is used for panel data analysis. Results indicate that volatility on bank stock returns has increased after 2008 and the implementation of the Basel II. Result is statistically very significant and robustness has been verified in different model specifications. The result of this study contradicts with the goal of the Basel II about banking system stability. Banking procyclicality and wrong incentives for regulatory arbitrage under asymmetric information explained in theoretical part may explain this result. On the other hand, simultaneously with the implementation of the Basel II, the global financial crisis emerged and caused severe losses in banks and increased stock volatility. However, it is clear that supervision and regulation was unable to prevent the global financial crisis. After the financial crisis, supervision and regulation have been reformed globally. The main problems of the Basel II, examined in the theoretical part, have been recognized in order to prevent problems of procyclicality and wrong incentives in the future.